The effect of object compliance on the velvet hand illusion - Pasqualotto, Achille (2021)
Movement of a grid of bars between the two hands creates the tactile illusion of a velvet-like material, namely, the velvet hand illusion (VHI). It was recently proposed that the VHI is caused by a masking effect; bar movement suppresses conscious perception of tactile inputs from the opposing hand. If this hypothesis sufficiently explains the VHI, the physical properties of the opposing hand should not affect the illusion. Another hypothesis suggests that the integration of inputs from the grid of bars and the hands plays a critical role in the VHI. To compare these two hypotheses, the VHI was elicited under two conditions; the grid of bars was between one hand and a soft texture or the grid of bars was between one hand and a hard texture. A hand was stimulated by moving bars while contacting the stationary texture held by the opposing hand. The grid of bars with the soft texture induced a stronger illusion and softer feeling than that with the hard texture. This result supports the integration hypothesis in which tactile inputs from both bars and textures attached to the opposing hand are integrated.